A Look Back: Education in the media, as seen in Kappan. (December 2019) - Preston, Teresa
In this monthly Kappan column, Teresa Preston shares a sampling of what past Kappan authors have written about the interactions between schools and the media. In the 1940s, authors began encouraging educators to build relationships with local media outlets, both to show they were meeting community expectations and to counter false narratives. In later decades, authors analyzed how schools and teachers were depicted in newspapers, in fiction, on television, and in movies. The picture painted was often grim. An especially persistent narrative that several authors across the decades sought to debunk was the idea that schools are failing. This idea doesn't necessarily stand up to close scrutiny .